Effects of a concept mapping-based two-tier test strategy on students' digital game-based learning performances and behavioral patterns. (November 2021) - Li, Feng-Ying; Hwang, Gwo-Jen; Chen, Pei-Ying; Lin, Yu-Jung
Abstract: This study explored the effects of a Concept Mapping-based Two-tier Test Gaming (CM-TTG) approach on learning achievement. Specifically, the two-tier test was employed as a learning diagnosis tool, and concept maps were utilized as the learning strategies to improve the students' learning achievement. To investigate the effectiveness of the proposed approach, a quasi-experimental design was applied to compare the learning achievement, learning motivation, flow experience, and cognitive loads of ninth-grade students using the CM-TTG approach and those using the conventional two-tier test-based gaming approach; moreover, the behavioral patterns of the experimental group and the control group using the different approaches as well as low- and high-achievers in the CM-TTG were analyzed as well. The results of the study showed that the concept-mapping strategy used with the two-tier test digital game-based learning could significantly improve the students' learning achievement. There were no significant differences in the learning motivation, flow experience, or cognitive loads of the two groups. Besides, the average scores of the two groups' learning motivation and flow experience were above 3.0, and those of their cognitive load ratings were below 3.0. It is inferred that the CM-TTG approach did not have a significant impact on the students' cognitive load, learning motivation, or flow experience. However, an examination of the participants' learning behavior patterns in the experimental group revealed that there were distinct differences between high-achieving and low-achieving students, as the former would actively build connections between concept maps and learning tasks to help them achieve the learning goals, while the low-achieving students would feel lost in the game without enforced instructions. Finally, through interviews, we analyzed and synthesized key factors impacting the students' learning achievements with the CM-TTG approach to serve as a reference for future research. Graphical abstract: Image 1 Highlights: A Concept Mapping-based Two-tier Test Gaming approach was proposed. A quasi-experimental design was applied to examine ninth-grade students. Students' learning motivation, flow experience, and cognitive loads were probed. The proposed approach significantly improved the students' learning achievement. The students' learning behavior patterns were analyzed and compared.